Facile synthesis of ZnPc nanoflakes for cold cathode emission. Issue 48 (29th April 2016) - Samanta, Madhupriya; Ghorai, Uttam Kumar; Das, Biswajit; Howli, Promita; Das, Swati; Sen, Dipayan; Chattopadhyay, Kalyan Kumar
Abstract : Field emission characteristics of well resolved ZnPc nanoflakes through hydrothermal method and simulation via finite element method. Abstract : The challenge of developing two dimensional metal phthalocyanine nanostructures by controlling the reaction protocols is successfully addressed in the present work by synthesizing zinc phthalocyanine (ZnPc) novel nanoflakes using a simple low temperature hydrothermal route. The as synthesized samples were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), ultra-violet visible spectrometer (UV-Vis), X-ray photoelectron spectroscopy (XPS) and field emission scanning electron microscope (FESEM). The field emission or cold cathode emission characteristics of these phthalocyanine nanostructures have been reported for the first time here and it is shown that as prepared nanoflakes can act as electron field emitter having a turn-on field 4.7 V μm −1 at a current density of 1 μA cm −2 for an inter electrode distance of 130 μm. The local electric field distributions around nanoflakes were also further studied theoretically using a finite element method. The obtained results indicate that ZnPc nanoflakes are the potential candidate for electron emission based applications such as vacuum nanoelectronic devices and field emission display devices.